2022
DOI: 10.1177/02610183221088461
|View full text |Cite
|
Sign up to set email alerts
|

Navigating multiple pandemics: A critical analysis of the impact of COVID-19 policy responses on gender-based violence services

Abstract: COVID-19 illustrated what governments can do to mobilise against a global threat. Despite the strong governmental response to COVID-19 in Canada, another ‘pandemic’, gender-based violence (GBV), has been causing grave harm with generally insufficient policy responses. Using interpretive description methodology, 26 interviews were conducted with shelter staff and 5 focus groups with 24 executive directors (EDs) from GBV service organizations in Ontario, Canada. Five main themes were identified and explored, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Related to long term mental health concerns, the public health pandemic of violence against women increased all over the world. Canada was no exception, with rates approximately double that of pre-pandemic times ( 31 ). Women survivors struggle with depression, substance use, and PTSD ( 32 ).…”
Section: Health Impacts Of Racism On Bipoc Communitiesmentioning
confidence: 99%
“…Related to long term mental health concerns, the public health pandemic of violence against women increased all over the world. Canada was no exception, with rates approximately double that of pre-pandemic times ( 31 ). Women survivors struggle with depression, substance use, and PTSD ( 32 ).…”
Section: Health Impacts Of Racism On Bipoc Communitiesmentioning
confidence: 99%
“…Applied in complex IPV interventions, TVIC is a way to ensure provider education and practice are both safe and structurally competent [62,93,94,95]. It is also showing promise in related areas of practice [6].…”
Section: What Makes Ipv Interventions Successful?mentioning
confidence: 99%
“…Intimate partner violence (IPV), defined as "behaviour within an intimate relationship that causes or has the potential to cause physical, sexual, or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse, and controlling behaviours" (World Health Organization (WHO)) [1], is a major public health crisis [2], with global data from 2018 indicating that 27% of women experience IPV in their lifetime, and 13% in the past year [3•]. IPV, and responses to it, has been made significantly worse by the COVID-19 pandemic [4,5] with multiple pre-and co-existing pandemics coming together to further exacerbate both prevalence and incidence of IPV, and the ability to balance adequate service responses for survivors with pandemic restrictions intended to curb disease spread [6]. The health and social consequences of IPV on survivors, especially women, and on families and society are well-documented, including worse physical and mental health [7], increased health risk behaviors [8,9,10], greater harm to children exposed to IPV [11,12], and significant costs to health and social services, and entire economies [13•, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the accepted abstracts, several cross‐cutting themes were identified that highlight the complex nature of gendered violence. The COVID‐19 pandemic and its economic, health and social reverberations were top‐of‐mind for many (Carter‐Snell et al, 2022; Gregory & Williamson, 2022a; Jaradat, 2022; Mantler & Wathen, 2022; Yakubovich & Shastri, 2022). The pandemic also brought into stark relief the broader structural forces that compound the risk of violence and hamper healing for those at the intersection of multiple marginalized identities (Alexander et al, 2022; Alhusen et al, 2022; Coelho et al, 2022; Gonzalez‐Guarda et al, 2022).…”
Section: Emerging Global Issuesmentioning
confidence: 99%